The influence of trinexapac-ethyl on growth and quality of Bermuda grass (Cynodon dactylon cv. Satiri) - Rosidi, Nur Adila; Juraimi, Abdul Shukor; Uddin, Md. Kamal; Alam, Md. Amirul (WFL Publisher, 2013)
The experiment was conducted at Unit Latihan Turf, Taman Pertanian Universiti, Universiti Putra Malaysia (UPM) to determine the influence of a growth retardant (Trinexapac-Ethyl: Primo®) on growth and quality of Bermuda grass (Cynodon dactylon cv. Satiri). Different concentrations of the growth retardant (0, 0.34, 0.76, 1.02 and 1.36 L/ha Primo®) were used to find out its influence on growth and quality of the grass. Growth and quality in terms of leaf length, leaf color, internodes length, root fresh and dry weight and shoot fresh and dry weight were determined. Results showed that different concentrations of Primo® had significant influences on growth and quality of Bermuda grass. Based on this data, Primo® at concentration of 0.76 L/ha produced the good quality Bermuda grass in comparison to other doses of Primo® used in this experiment.